Wissenschaft als Grenzwissenschaft Hans Bender (1907-1991) und die deutsche Parapsychologie - Lux, Anna (Okkulte Moderne, 2021)
How does a field of knowledge achieve legitimacy as science? The focus of this historical analysis is on the ever-controversial "fringe discipline" of parapsychology and its most important advocate Hans Bender. It analyzes the history of this contingent discipline, examining the interaction between science, society, and the public media in manufacturing scientific legitimacy.